2014
DOI: 10.1007/s10570-014-0213-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative molecular dynamics study of crystalline, paracrystalline and amorphous states of cellulose

Abstract: The quintessential form of cellulose in wood consists of microfibrils that have high aspect ratio crystalline domains embedded within an amorphous cellulose domain. In this study, we apply unitedatom molecular dynamics simulations to quantify changes in different morphologies of cellulose. We compare the structure of crystalline cellulose with paracrystalline and amorphous phases that are both obtained by high temperature equilibration followed by quenching at room temperature. Our study reveals that the parac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 54 publications
7
111
0
2
Order By: Relevance
“…polymorphs II, III and IV. Cellulose also exists in amorphous form which is soluble and can be easily digested by enzymes (Kulasinski, Keten, Churakov, Derome, & Carmeliet, 2014).…”
Section: Structure Of Lignocellulosementioning
confidence: 99%
“…polymorphs II, III and IV. Cellulose also exists in amorphous form which is soluble and can be easily digested by enzymes (Kulasinski, Keten, Churakov, Derome, & Carmeliet, 2014).…”
Section: Structure Of Lignocellulosementioning
confidence: 99%
“…Through a combination of computational (Dri et al, 2013;Kulasinski et al, 2014;Sinko et al, 2014;Wu et al, 2013) and experimental (Kong and Eichhorn, 2005;Lindman et al, 2010;Nishiyama et al, 2002;Tashiro and Kobayashi, 1991) studies, it has been established that both hydrogen bonding and secondary van der Waals interactions play a crucial role in determining the emergent macroscale properties of these crystals. For Iβ cellulose, commonly called "natural" cellulose, it has been shown that hydrogen bonding is dominant along the (110) plane while van der Waals interactions are dominant along the (200) plane (Sinko et al, 2014), with these planes indicated in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller nanocrystals exhibit lower fracture surface energy, whereas larger crystals have reduced surface area to volume ratio, making this intermediate length-scale optimal for nanocomposites. While a number of recent studies have characterized the elastic and fracture properties of crystalline cellulose at the molecular level (Eichhorn and Davies, 2006;Kulasinski et al, 2014;Matthews et al, 2006;Sinko et al, 2014), the focus has been on the axial and transverse tensile properties of individual CNCs. Much less is known about interfaces between multiple CNCs, or shear failure of CNCs under various loading scenarios relevant to nanocomposites and neat films (Chen et al, 2009;Cox, 1952;Gao and Li, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, united-atom MD simulations were used to quantify changes in different morphologies of cellulose to reveal that the semicrystalline phase may be an intermediate, kinetically arrested phase formed at amorphous cellulose formation. 73 MD simulation showed in Ib crystalline cellulose that elastic modulus, Poisson's ratio, yield stress and strain, and ultimate stress and strain are highly anisotropic, and that although properties that describe elastic behavior of the material are independent of strain rate, yield and ultimate properties increase with increasing strain rate. 74 In another MD study, 75 the fracture energy of crystalline cellulose was found to depend on crystal width, due to edge defects that significantly reduce the fracture energy of small crystals but have a negligible effect beyond a critical width.…”
Section: Applications Of Atomistic Simulations In Understanding Smallmentioning
confidence: 99%